PERANCANGAN KEMASAN USAHA RENDANG BOLA-BOLA UNI SOFIE BUKITTINGGI - HANSRIAN ZURIHNAL, Dini Faisal, S.Ds., M.Ds., Dra. Zubaidah, M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Rendang is a dish with processed meat from Minangkabau. Each region is unique when processing Rendang. The home business of the Uni Sofie, which is located in Bukittinggi, processes tuna meat into Rendang. Fish meat is ground, and made round like meatballs. The preparation is called "Rendang Bola-bola". Even with a unique appearance, Rendang Bola-bola has its drawbacks. Business identity and product safety have not been fully implemented on the packaging. The purpose of designing the packaging of Rendang Bola-bola Uni Sofie is to protect the product with a business identity that is easily understood by consumers.Qualitative descriptive method is used in designing, collecting data through observation and interviews from the owner. The SWOT data analysis method is a problem solving by raising excellence to get the right layout, typography, and color for Rendang Bola-bola Uni Sofie. The addition of media such as X-banners, posters, flyers, aprons, business cards, paper bags, and posters aims to support the main media packaging.With the design of Rendang's business packaging design Rendang Bola-bola Uni Sofie's in Bukittinggi, can attract the attention of buyers and improve the existence of food businesses in the city of Bukittinggi.Keywords: Packaging, Rendang Bola-bola, design.